Assessing Bus Performance Rating in Kajang, Selangor - Norhisham S.; Ismail A.; Sidek L.M.; Borhan M.N.; Zaini N.; Yen A.T.G. (Institute of Physics Publishing, 2023)
Buses; Mass transportation; Rapid transit; Sustainable development; Telecommunication services; Travel time; Bus scheduling; Hours of services; Mass rapid transit; Passenger loads; Performance ratings; Service frequency; Transit capacity; Quality of service